Ghost in the Shell: Is Ownership of a Digital File Possible? - Medvedevaitė, Akvilė; Birštonas, Ramūnas (Teisė, 2025)
The article examines whether a digital file can be considered an object of ownership under Lithuanian property law. While the Lithuanian Civil Code stipulates that ownership can extend not only to tangible objects but also to other forms of property, there are no clearly defined legal criteria for determining which objects fall within this category and can be recognized as ownership objects. The analysis includes Case Law from the European Court of Justice and national courts of other jurisdictions, which generally take a sceptical stance on recognizing digital files as independent objects of ownership. The article highlights that digital files fundamentally differ from traditional ownership objects, as their reproduction is unrestricted, and identical copies can exist simultaneously, thereby challenging the applicability of the principle of specificity. Considering these factors, the article concludes that digital files do not meet the requirements of specificity and the owner’s direct control, thus making their recognition as ownership objects under Lithuanian law problematic.